Comparison of isoflurane and propofol for maintenance of anesthesia in dogs with intracranial disease undergoing magnetic resonance imaging. (10th May 2014) - Caines, Deanne; Sinclair, Melissa; Valverde, Alexander; Dyson, Doris; Gaitero, Luis; Wood, Darren
Abstract Objective To compare isoflurane and propofol for maintenance of anesthesia and quality of recovery in client‐owned dogs with intracranial disease undergoing magnetic resonance imaging (MRI). Study design Prospective, randomized, clinical trial. Animals Twenty‐five client‐owned dogs with intracranial pathology, 13 females and 12 males, ages 11 months to 13 years, weighing between 3.0 and 48.0 kg. Methods Each dog was randomly assigned to receive propofol or isoflurane for maintenance of anesthesia. All dogs were not premedicated, were administered propofol intravenously to effect for induction, intubated and mechanically ventilated to maintain an end‐tidal carbon dioxide tension 30–35 mmHg (4.0–4.7 kPa). Temperature and cardiac output were measured pre‐ and post‐MRI. Scores for mentation, neurological status, ease of maintenance, and recovery were obtained pre‐ and post‐anesthesia. Pulse oximetry, end‐tidal gases, arterial blood pressure, heart rate (HR) and requirements for dopamine administration to maintain mean arterial pressure (MAP) >60 mmHg were recorded throughout anesthesia. Results End‐tidal isoflurane concentration was 0.73 ± 0.35% and propofol infusion rate was 292 ± 119 μg kg−1 minute−1. Cardiac index was higher, while HR was lower, with propofol than isoflurane in dogs younger than 5 years, but not in older dogs. Dogs maintained with isoflurane were 14.7 times more likely to require dopamine than propofol dogs. Mentation and maintenance scores and temperature were not different. MAP and diastolic arterial pressure were higher in the propofol group. Recovery scores were better with propofol, although times to extubation were similar. Change in neurological score from pre‐ to post‐anesthesia was not different between treatments. Conclusions Dogs maintained with propofol during MRI had higher arterial pressures, decreased requirements for dopamine, and better recovery scores, compared to dogs maintained with isoflurane. Clinical relevance Propofol anesthesia offered cardiovascular and recovery advantages over isoflurane during MRI in dogs with intracranial disease in this study.